Organization of cubic CeO2 nanoparticles on the edges of self assembled tapered ZnO nanorods via a template free one-pot synthesis: significant cathodoluminescence and field emission properties - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Patil, Kashinath R.; Koinkar, Pankaj M.; More, Mahendra A.; Murakami, Ri-ichi (Journal of Materials Chemistry, 2012)
The present investigation explores the controlled architecture of a CeO2-ZnO nanocomposite via a template-free, low temperature, facile single step solvothermal approach. This complex architecture depicts cubic single crystalline CeO2 nanoparticles (size similar to 15 nm) grown on the edges of tapered ZnO nanorods with definite orientations and alignments. The formation of wurtzite ZnO, cubic CeO2 and the coexistence of Ce3+ and Ce4+ on the surface of the CeO2-ZnO nanocomposites are confirmed using various characterization tools. The finding of such unique nanostructures by a facile method is exemplified by a plausible growth mechanism. Surprisingly, the aqueous mediated ultrasonication reaction conferred the formation of crystalline ZnO nanotubes of diameter similar to 50 nm. Spatially resolved cathodoluminescence spectra are obtained by linearly scanning an individual CeO2-ZnO nanorod along its length, which reveals the size-dependent surface effects. Interestingly, such hybrid CeO2-ZnO nanoarchitecture is observed to exhibit enhanced field emission properties, demonstrating better current stability as compared to other ZnO nanostructures. This is attributed mainly to strong surface interactions between the Ce-ionic species and the ZnO nanorods. Herein, a soft-chemical approach is used for the first time to architect a binary oxide nanostructure, which is otherwise accomplished using high temperature techniques, as reported elsewhere. Also, the present work not only gives insight into understanding the hierarchical growth behaviour of the CeO2-ZnO nanocomposite in a solution phase synthetic system, but also provides an efficient route to enhance the field emission performance of ZnO nanostructures, which could be extended to other potential applications, such as chemical sensors, optoelectronic devices and photocatalysts.